2009
DOI: 10.1073/pnas.0906029106
|View full text |Cite
|
Sign up to set email alerts
|

Glacier loss on Kilimanjaro continues unabated

Abstract: climate change ͉ climatology ͉ glacier retreat ͉ ice cores ͉ paleoclimate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 25 publications
6
81
0
2
Order By: Relevance
“…Climate change is significantly affecting high elevation mountain areas across the planet and is occurring much faster than was previously predicted (Bradley et al 2009;Dyurgerov 2003;IARU 2009;IPCC 2007a;Nogues-Bravo et al 2007;Stewart 2009;Thompson et al 2009;Viviroli et al 2007;WMO 2009). Globally, a significant percentage of humanity is dependent upon the ecological services and water resources that mountain glaciers provide to downstream populations and their rapid recession has widespread implications for future water availability, agricultural production and human vulnerability (Alcamo et al 2007;Barnett et al 2005;Barry and Seimon 2000;Fagre et al 2003;IPCC 2007a;Kundzewicz et al 2008;Milner et al 2009;Morton 2007;Orlove 2009;Rosenzweig et al 2004; Thompson et al 2006;Viviroli et al 2007;Xu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is significantly affecting high elevation mountain areas across the planet and is occurring much faster than was previously predicted (Bradley et al 2009;Dyurgerov 2003;IARU 2009;IPCC 2007a;Nogues-Bravo et al 2007;Stewart 2009;Thompson et al 2009;Viviroli et al 2007;WMO 2009). Globally, a significant percentage of humanity is dependent upon the ecological services and water resources that mountain glaciers provide to downstream populations and their rapid recession has widespread implications for future water availability, agricultural production and human vulnerability (Alcamo et al 2007;Barnett et al 2005;Barry and Seimon 2000;Fagre et al 2003;IPCC 2007a;Kundzewicz et al 2008;Milner et al 2009;Morton 2007;Orlove 2009;Rosenzweig et al 2004; Thompson et al 2006;Viviroli et al 2007;Xu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling by Hastenrath (2010) and others (Mölg et al, 2003b;Mölg et al, 2009b;Mölg and Kaser, 2011) has confirmed that solar radiation forcing continues to be important for the lateral retreat of ice cliffs and ice thinning on Kilimanjaro. Air temperature changes on the other hand are at present relatively unimportant in controlling ice-field mass balance in this high elevation dry environment, although presence of meltwater found in cores suggests that air temperature must at least occasionally rise above freezing (see Thompson et al, 2009). Despite this, mean summit temperatures are currently well below freezing (Kaser et al, 2004;Duane et al, 2008;Pepin et al, 2010), and advective melting due to warmer air temperatures is relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…This horizontal lowering is again broadly in agreement with other research. Thompson et al (2009) reports a minimum lowering of 1.9 m for the NIF between 2000 and 2007, which equates to 0.27 m yr -1 . The reduced rate in period 2 coincides with an El Niño event in East Africa that is known to encourage wetter conditions in general (Kijazi and Reason, 2009).…”
Section: Surface Loweringmentioning
confidence: 99%
See 2 more Smart Citations